Actor movement expression of the physical being : a movement handbook for actors - Ewan, Vanessa 1960-; Green, Debbie 1956- (London, UK Bloomsbury Methuen Drama, 2015)
"Actor Movement offers enabling tools to explore, examine and develop movement techniques to fine-tune the actor's intuitive physical response"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Movement (Acting)